2021
DOI: 10.1186/s13075-021-02454-6
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of low-dose intravenous arsenic trioxide in systemic lupus erythematosus: an open-label phase IIa trial (Lupsenic)

Abstract: Background Lupus animal model has shown that arsenic trioxide (ATO), a treatment of acute promyelocytic leukaemia, could be effective in SLE. This is the first clinical study to determine the safety and efficacy of a short course of intravenous ATO in patients with active SLE. Methods This phase IIa, open-label, dose-escalating study enrolled 11 adult SLE patients with a non-organ threatening disease, clinically active despite conventional therapy.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 42 publications
(11 reference statements)
0
9
0
Order By: Relevance
“…Arsenic trioxide (ATO) is a well-known traditional Chinese drug used to treat acute promyelocytic leukemia (APL) [29,30]. In recent years, several reports have shown that ATO is a promising treatment for dysregulated immune disease [31][32][33][34]. Moreover, ATO could improve the clinical symptoms in mice with sclerodermatous GVHD [35].…”
Section: Introductionmentioning
confidence: 99%
“…Arsenic trioxide (ATO) is a well-known traditional Chinese drug used to treat acute promyelocytic leukemia (APL) [29,30]. In recent years, several reports have shown that ATO is a promising treatment for dysregulated immune disease [31][32][33][34]. Moreover, ATO could improve the clinical symptoms in mice with sclerodermatous GVHD [35].…”
Section: Introductionmentioning
confidence: 99%
“…Arsenic trioxide (ATO), used for treating acute promyelocytic leukemia, has shown the potential to treat lupus-like disease processes in animal models ( Hamidou et al, 2021 ). In a phase IIa clinical study, researchers evaluated the efficacy and safety of intravenous ATO treatment for patients with active SLE ( Hamidou et al, 2021 ).…”
Section: Results and Context Of Included Studiesmentioning
confidence: 99%
“…Arsenic trioxide (ATO), used for treating acute promyelocytic leukemia, has shown the potential to treat lupus-like disease processes in animal models ( Hamidou et al, 2021 ). In a phase IIa clinical study, researchers evaluated the efficacy and safety of intravenous ATO treatment for patients with active SLE ( Hamidou et al, 2021 ). The outcome of this study shows that ATO as a complementary treatment resulted in a decrease in corticosteroid dosage from 11.25 mg/day at baseline to 6 mg/day at week 24 ( Hamidou et al, 2021 ).…”
Section: Results and Context Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental models have greatly improved our understanding of the pathogenesis of GvHD and have led to newer approaches targeting different components of immune dysregulation. ATO is a drug recognized in the treatment of acute promyelocytic leukemia ( 12 , 13 ) and is also a therapeutic alternative tested in clinical studies in acute ( 14 , 15 ) and chronic GvHD ( 16 , 17 ) but also lupus progression ( 18 ). In a mouse model of cGvHD, the administration of ATO increased the production of reactive oxygen species (ROS), especially H 2 O 2 and hydroxyl radicals ( 16 ), which induced apoptosis of activated alloreactive lymphocytes and plasmacytoid dendritic cells ( 19 ), leading to a reduction of systemic inflammation and fibrosis of the skin and lung ( 16 ).…”
Section: Introductionmentioning
confidence: 99%